Overview of Bifluid-based Photovoltaic Thermal (PVT) Systems - Nurul Shahirah Binti Rukman; Ahmad Fudholi; Saleem H. Zaidi; Kamaruzzaman Sopian (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This review presents various research and development, as well as design and performances of bifluid-based PVT systems. Moreover, the development of PVT system is a very promising area of research. PVT systems using in various applications, such as solar drying, solar cooling, water heating, desalination, and pool heating. With the recognition of the potentials and contributions of PV system, considerable research has been conducted to attain the most advancement which may produce reliable and sustainable PVT system. The cooling system’s design refers to the absorber design which mostly focuses on water and air-based PVT systems. An air-based system has been developed through different absorber configurations, air flow modes and single- or double-pass design. Bifluid-based PVT system is used to remove heat accumulated in a PV panel and reuses the waste heat (hot air and water) in an appropriate way. PV, thermal and PVT efficiencies of bifluid PVT systems were 6.6%-18.6%, 31%–90% and 60%-83%, respectively.